The bricoleur lighting designer and their luminous creations: artifacts, bricolages, and artisanal practices (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article investigates how the concept of the bricoleur, formulated by Claude Lévi-Strauss, contributes to understanding the creative process of lighting design in stage performance. It is based on the hypothesis that the lighting designer mobilizes an inventory of cultural references, consisting of observations, perceptions of reality, and technical and technological knowledge, in the development of the lighting composition. From this perspective, luminous artifacts are analyzed as materializations of creative imagination, in dialogue with Lev Vigotski's concept of crystallized imagination, understanding the lighting designer as a bricoleur in the construction of aesthetic experiences.
Keywords: stage lighting; Bricoleur; luminous artifacts; imagination; creativity